2018
DOI: 10.1093/police/pay011
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Changing Patterns of Behaviour Leading to Increased Detentions by the Police under Section 136 of the Mental Health Act 1983

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 13 publications
1
25
0
Order By: Relevance
“…In many instances, there is thus a shared responsibility for the created failure demand. An example of this is in response to mental health cases, which havefor a variety of reasonshave increasingly become a driver of police calls for service (Patel et al 2016, Thomas andForrester-Jones 2018). For example, the number of people detained by the police in the UK for compulsory treatment under the provisions of the Mental Health Act 1983 (i.e.…”
Section: Failure Demand and Service Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…In many instances, there is thus a shared responsibility for the created failure demand. An example of this is in response to mental health cases, which havefor a variety of reasonshave increasingly become a driver of police calls for service (Patel et al 2016, Thomas andForrester-Jones 2018). For example, the number of people detained by the police in the UK for compulsory treatment under the provisions of the Mental Health Act 1983 (i.e.…”
Section: Failure Demand and Service Qualitymentioning
confidence: 99%
“…For example, the number of people detained by the police in the UK for compulsory treatment under the provisions of the Mental Health Act 1983 (i.e. mental health cases handled by the police) has increased from 40,000 in 2003/04 to over 63,000 in 2015/16 (Thomas and Forrester-Jones 2018). As such, the police are increasingly becoming the 'last resort' and a 'de-facto 24 h social service' (Steadman et al 1995, Lamb et al 2002, Patel et al 2016.…”
Section: Failure Demand and Service Qualitymentioning
confidence: 99%
“…2327 Other recent research into police attitudes, notably that of Thomas and Forrester-Jones, lends some support to Bendelow’s ‘pastoral’ perspective by suggesting that it interacts with a ‘risk-averse culture’ within the police that itself contributed to the s136 rise. 28 The hypothesis here is that as mental-health issues became increasingly part of the police’s ‘core business’, so an awareness of suicide risk and pastoral concerns combined together to increase the use of s136 and the removal of the detainee to the increasingly available HBPOS rather than to a police cell.…”
Section: Cultural Factorsmentioning
confidence: 99%
“…Self-harm may also be relevant for a longer-term causal analysis of the s136 rise in the aftermath of the GFC and austerity in two ways: first because several studies have indicated that a significant reason for the police’s use of s136 occurs when the detainee is at risk of self-harm and/or suicide, including the already cited work of Thomas and Forrester-Jones; and second because Bendelow’s research emphasised how the decision making of police officers was influenced by their non-medical classifications of mental distress. 24,25,28 ‘Detentions were coded as “Suicidal”’, Bendelow and colleagues observed, ‘if the records had stated the person was detained because of concerns that they intended to end their life, had taken an overdose etc.’. 24 This is significant for what Loughran called the ‘threshold’ problem: over time, police attitudes have reduced the threshold which needs to be met for s136 to be implemented, and this reduction seems to be related to their increasing awareness of suicidal and self-harming behaviour.…”
Section: Economic Factorsmentioning
confidence: 99%
See 1 more Smart Citation